Image_19.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
Goddess Lakshmi in her form as Gajalakshmi (Lakshmi garlanded by a pair of elephants) hangs on the wall of the stall. Lakshmi is the Hindu goddess of wealth and prosperity. The Koli women offer incense to Lakshmi in the morning, before business commences, and after sunset, the same way they do at their homes.